Evaluation of bioactive glass and demineralized freeze dried bone allograft in the treatment of periodontal intraosseous defects: A comparative clinico-radiographic study - Kishore Kumar Katuri; P Jaya Kumar; Chakrapani Swarna; D Narasimha Swamy; Kurumathur V Arun (Wolters Kluwer Medknow Publications, 2013)
Aim: The purpose of this study was to evaluate the efficacy of demineralized freeze dried bone allograft (DFDBA) and bioactive glass by clinically and radiographically in periodontal intrabony defects for a period of 12 months. Materials and Methods: Ten systemically healthy patients diagnosed with chronic periodontitis, with radiographic evidence of at least a pair of contralateral vertical osseous defects were included in this study. Defect on one-side is treated with DFDBA and the other side with bioactive glass. Clinical and radiographic measurements were made at baseline 6 month and 12 month after the surgery. Results: Compared to baseline, the 12 month results indicated that both treatment modalities resulted in significant changes in all clinical parameters (gingival index, probing depth, clinical attachment level (CAL) and radiographic parameters (bone fill); P < 0.001FNx01). However, sites treated with DFDBA exhibited statistically significantly more changes compared to the bioactive glass in probing depth reduction (2.5 ± 0.1 mm vs. 1.8 ± 0.1 mm) CAL gain 2.4 ± 0.1 mm versus 1.7 ± 0.2 mm; ( P < 0.001FNx01). At 12 months, sites treated with bioactive glass exhibited 56.99% bone fill and 64.76% bone fill for DFDBA sites, which is statistically significant ( P < 0.05FNx01). Conclusion: After 12 months, there was a significant difference between the two materials with sites grafted with DFDBA showing better reduction in probing pocket depth, gain in CAL and a greater percentage of bone fill when compared to that of bioactive glass.